The response of Naegleria gruberi to oxidative stress - Malych, Ronald; Füssy, Zoltán; Ženíšková, Kateřina; Arbon, Dominik; Hampl, Vladimír; Hrdý, Ivan; Sutak, Robert (Metallomics, 2022)
Aerobic organisms require oxygen for respiration but must simultaneously cope with oxidative damages inherently linked with this molecule. Unicellular amoeboflagellates of the genus Naegleria, containing both free-living species and opportunistic parasites, thrive in aerobic environments. However, they are also known to maintain typical features of anaerobic organisms. Here, we describe the mechanisms of oxidative damage mitigation in Naegleria gruberi and focus on the molecular characteristics of three noncanonical proteins interacting with oxygen and its derived reactive forms. We show that this protist expresses hemerythrin, protoglobin, and an aerobic-type rubrerythrin, with spectral properties characteristic of the cofactors they bind. We provide evidence that protoglobin and hemerythrin interact with oxygen in vitro and confirm the mitochondrial localization of rubrerythrin by immunolabeling. Our proteomic analysis and immunoblotting following heavy metal treatment revealed upregulation of hemerythrin, while rotenone treatment resulted in an increase in rubrerythrin protein levels together with a vast upregulation of alternative oxidase. Our study provided new insights into the mechanisms employed by N. gruberi to cope with different types of oxidative stress and allowed us to propose specific roles for three unique and understudied proteins: hemerythrin, protoglobin, and rubrerythrin.
Keywords: kyslík; oxidační stres; Hemerythrin; Naegleria; Proteomics; hemerythrin; Oxygen; proteomika; Oxidative Stress